2003
DOI: 10.4049/jimmunol.171.11.5988
|View full text |Cite
|
Sign up to set email alerts
|

Function of Bruton’s Tyrosine Kinase during B Cell Development Is Partially Independent of Its Catalytic Activity

Abstract: The Tec family member Bruton’s tyrosine kinase (Btk) is a cytoplasmic protein tyrosine kinase that transduces signals from the pre-B and B cell receptor (BCR). Btk is involved in pre-B cell maturation by regulating IL-7 responsiveness, cell surface phenotype changes, and the activation of λ L chain gene rearrangements. In mature B cells, Btk is essential for BCR-mediated proliferation and survival. Upon BCR stimulation, Btk is transphosphorylated at position Y551, which promotes its catalytic activity and subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
83
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 43 publications
5
83
0
Order By: Relevance
“…1 also demonstrates independent roles for Btk and PLCc2 in pre-BCR down-regulation and development beyond the pre-B stage. Some functions of Btk in pre-B cells do not require its catalytic activity, including control of Igk expression [6] and suppression of pre-B malignancies [30]. These are likely candidates for PLCc2-independent actions of Btk since a major mode of PLCc2 activation is phosphorylation by Btk [26,27].…”
Section: Igk Usage Is Regulated By Both Btk and Plcc2mentioning
confidence: 99%
See 2 more Smart Citations
“…1 also demonstrates independent roles for Btk and PLCc2 in pre-BCR down-regulation and development beyond the pre-B stage. Some functions of Btk in pre-B cells do not require its catalytic activity, including control of Igk expression [6] and suppression of pre-B malignancies [30]. These are likely candidates for PLCc2-independent actions of Btk since a major mode of PLCc2 activation is phosphorylation by Btk [26,27].…”
Section: Igk Usage Is Regulated By Both Btk and Plcc2mentioning
confidence: 99%
“…3). Thus, normal Igk usage in newly generated B cell populations requires the expression of Btk and PLCc2 but not Btk kinase activity [6], suggesting a role for the PIP5K pathway [5].…”
Section: Igk Usage Is Regulated By Both Btk and Plcc2mentioning
confidence: 99%
See 1 more Smart Citation
“…2C) and micro-architecture of the spleen (data not shown). Moreover, we have previously found that Y223 phosphorylation is not essential for Btk function in vivo: Y223F-Btk can fully correct the features of the Btk-deficient phenotype, including pre-B-cell B-1 cell development, serum IgM levels and TI-II responses [27].The complex phenotype of mice with constitutively activated Btk largely resembles that of other Tg or knock-out mice with increased BCR signaling [12][13][14][15][16][17][18][19]. These mice also contain fewer follicular B cells, increased numbers of B-1 B cells, together with B-cell hyperresponsiveness and autoimmunity.…”
mentioning
confidence: 99%
“…The pleckstrin homology domain mutant E41K-Btk displayed robust transformation potential in a soft-agar assay, increased membrane localization and phosphorylation in quiescent cells, independent of PI3K activity [26]. This capacity was augmented by mutation of the main autophosphorylation site in the SH3 domain, Y223F, although the role of Y223 phosphorylation for Btk function in vivo remains unclear [22,27]. We have previously reported that expression of Tg E41K-Btk throughout the B-cell lineage resulted in an almost complete deletion of immature B cells in the BM, irrespective of the presence of the endogenous intact Btk gene [28].…”
mentioning
confidence: 99%